Mental health circumstances among health care workers and general public under the pandemic situation of COVID-19 (HOME-COVID-19). Issue 26 (26th June 2020) - Nochaiwong, Surapon; Ruengorn, Chidchanok; Awiphan, Ratanaporn; Ruanta, Yongyuth; Boonchieng, Waraporn; Nanta, Sirisak; Kowatcharakul, Woravut; Pumpaisalchai, Wanida; Kanjanarat, Penkarn; Mongkhon, Pajaree; Thavorn, Kednapa; Hutton, Brian; et al.
Abstract: Background: After the spread of the coronavirus disease 2019 (COVID-19) globally, upgraded quarantine and physical distancing strategy, strict infection measures, and government's strict lockdown have been abided to confront the spread of the COVID-19 in Thailand. During the COVID-19 pandemic, concerns about the mental health and psychosocial problems among health care workers and the general population are now arising. Yet, information on mental health and psychosocial problems among health care workers and the general population have not been comprehensively reported in Thailand. As such, we conduct a cross-sectional study, a national online survey to describe the short- and long-term consequences of the COVID-19 pandemic on mental health and psychosocial problems among health care workers and the general population in Thailand. Methods: This study is a repeated cross-sectional study, an open online voluntary national-based survey during the wave I (April 21–May 4, 2020) follow-up in the wave II (August 3–16, 2020), wave III (November 15–28, 2020), and a 1-year follow-up survey (wave IV: April 21–May 4, 2021) in Thailand. Health care workers at the hospitals and the adult general population will be invited to participate in the online survey via the SurveyMonkey that limits one-time participation per unique internet protocol address. The target sample size of at least 1182 health care workers and 1310 general populations will be required to complete the online survey for each wave of the survey. Sociodemographic characteristics and a set of measurement tools for mental and psychosocial problems for each subcohort including depression, anxiety, stress, resilient copings, neuroticism, perceived social support, wellbeing, somatic symptoms, insomnia, burnout (for healthcare workers), and public stigma toward COVID-19 infection (for the general population) will be collected. For all estimates of prevalence, we will weigh data for all wave analyses under the complex design of the survey. Subgroup analyses stratified by key characteristics will also be done to analyze the proportion differences. For the repeated cross-sectional survey, we will combine the data from the wave I to wave IV survey to analyze changes in the mental health status. We will perform multilevel logistic regression models with random intercepts to explore associations with individual-level and region-level/hospital-level predictors. We also plan to perform an ancillary systematic review and meta-analysis by incorporating data from our findings to all available evidence. Results: Our findings will provide information on the short- and long-term mental health status as well as the psychosocial responses to the COVID-19 outbreak in a national sample of health care workers and the general population in Thailand. Conclusion: This prospective, nationally based, a repeated cross-sectional study will describe the mental health status and psychosocial problems among health care workers and the general population in Thailand during the COVID-19 pandemic. Ethics and dissemination: Ethical approval for the study was obtained from the Faculty of Public Health and Faculty of Pharmacy, Chiang Mai University. The findings will be disseminated through public, scientific, and professional meetings, and publications in peer-reviewed journals. Thai Clinical Trials Registry (TCTR) registration number: TCTR20200425001.